Peran Hasil Tes Potensi Akademik Sebagai Prediktor Pencapaian Prestasi Belajar Tahun I Mahasiswa Keperawatan Stikes Panti Rapih - Puspasari, Scholastica Fina Aryu (Indonesian Academia Health Sciences Journal, 2020)
Objective: This study aims to identify the role of Academic Potential Test as the predictor of student achievement in first year in nursing program Methods: This research used quantitative research design with correlative methode involving 89 students in first year nursing diploma program.Results: This research obtained p value 0.02, means there is a significant correlation between Academic Potential Test and student achievement in first year Nursing Program.Conclusion: The Academic Potential Test could be the predictor ofÂ  student achievement in first year